Influence of alkali metal doping on surface properties and catalytic activity/selectivity of CaO catalysts in oxidative coupling of methane - Rane, V. H.; Chaudhari, Sopan T.; Choudhary, Vasant R. (Journal of Natural Gas Chemistry, 2008)
Surface properties viz. surface area, basicity/base strength distribution, and crystal phases) of alkali metal doped CaO (alkali metal/Ca = 0.1 and 0.4) catalysts and their catalytic activity/selectivity ill oxidative coupling of methane (OCM) to higher hydrocarbons at different reaction conditions (viz. temperature. 700 and 750 degrees C: CH(4)/O(2) ratio. 4.0 and 8.0 and space velocity. 5140-20550 cm(3). g(-1).h(-1)) have been investigated. The influence of catalyst calcination temperature on the activity/selectivity has also been investigated. The surface properties (viz. surface area, basicity/base strength distribution) and catalytic activity/selectivity of the alkali metal doped CaO Catalysts are strongly influenced by the alkali metal promoter and its concentration in the alkali metal doped CaO catalysts. An addition of alkali Metal promoter to CaO results in a large decrease in the surface area but a large increase in the surface basicity (strong basic sites) and the C(2+) Selectivity and yield of the catalysts in the OCM process. The activity and selectivity are strongly influenced by the catalyst calcination temperature. No direct relationship between surface basicity and catalytic activity/selectivity has been observed. Among the alkali metal doped CaO catalysts. Na-CaO (Na/Ca = 0.1. before calcination) catalyst (calcined at 750 degrees C), showed best performance (C(2+) selectivity of 68.8% with 24.7% methane conversion), whereas (lie poorest performance was shown by the Rb-Cao Catalyst in the OCM process.
Keywords: alkali metal doped CaO catalysts; basicity/base strength distribution; catalytic activity/selectivity; oxidative coupling of methane

Oxidative coupling of methane over La-promoted CaO catalysts: influence of precursors and catalyst preparation method - Rane, Vilas H.; Chaudhari, Sopan T.; Choudhary, Vasant R. (Journal of Natural Gas Chemistry, 2010)
The oxidative coupling of methane to C(2) hydrocarbons has been studied over a series of La-promoted CaO (La/Ca = 0.05) catalysts, prepared using different precursor salts for CaO and La(2)O(3) (viz. acetates, carbonates, nitrates and hydroxides) and catalyst preparation methods (viz. physical mixing of precursors, co-precipitation using ammonium carbonate/sodium carbonate as a precipitating agent), under different reaction conditions (temperature: 700-850 degrees C, CH(4)/O(2) ratio: 4.0 and 8.0, and GHSV: 51360 cm(3).g(-1).h(-1)). The surface area and surface basicity/base strength distribution of the catalysts have also been investigated. The surface properties and catalytic activity/selectivity of the La-promoted CaO catalysts vary from catalyst to catalyst depending on the catalyst precursors used and catalyst preparation method. The basicity/base strength distribution is strongly influenced by the precursors (for CaO and La(2)O(3)) and catalyst preparation method. Basicity (total and strong basic sites measured in terms of CO(2) chemisorbed at 50 degrees C and 500 degrees C, respectively) observed for the catalyst prepared by co-precipitation method is higher than that of the catalysts prepared by physical mixing method. The catalysts prepared by the nitrates of La- and Ca- and co-precipitated by the solution of sodium carbonate and ammonium carbonate exhibit different catalytic performance in OCM. The finding that no direct relationship between the surface basicity and catalytic activity/selectivity in OCM exists indicates that basicity is not solely responsible for obtaining high selectivity to C(2) hydrocarbons.
Keywords: basicity distribution; La-promoted CaO catalysts; oxidative coupling of methane